Innovation and entrepreneurship - Bessant, J. R.; Tidd, Joseph, 1960- (Hoboken : Wiley, 2024)
"This book has been developed specifically for students of Business and Management Studies, and for Science and Engineering students studying courses on innovation and/or entrepreneurship. It is designed to complement our best-selling text Managing Innovation: Integrating Technological, Market and Organizational Change (Eighth edition, John Wiley & Sons Ltd, 2024), which is focused more on the needs of specialist postgraduate and post-experience audiences. In this fourth edition, we were inspired by the pioneering scholars of entrepreneurship and innovation, such as Joseph Schumpeter and Peter Drucker, to attempt to re-integrate these two fields. For too long the two subjects have diverged into narrow disciplines, each suffering as a result: entrepreneurship has become preoccupied with small business creation and innovation dominated by new product development. In this text, we aim to reunite the study and practice of entrepreneurship and innovation. In Innovation and Entrepreneurship (fourth edition), we continue to take a unique position at the interface of these two fields, rather than a traditional narrow focus on one or the other. On the one hand, the Innovation field has a bias towards larger firms and formal processes, whereas on the other hand, the Entrepreneurship discipline is dominated by a focus on individuals, startups and small firms, but with little emphasis on the role of innovation. In contrast, here we adopt a view that aims to identify and explore the intersections and interactions between these two fields, such as entrepreneurship in larger organizations, and innovation in new enterprises and smaller firms. Integrating themes include social, sustainable and digital innovation and entrepreneurship"--
Revised edition of the authors' Innovation and entrepreneurship, [2015]
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Creative ability in business; Entrepreneurship